A The Influence of TikTok's Recommendation Algorithm (the ‘FYP Destiny’ Effect) and TikTok Live Chat on Purchase Decisions with Perceived Personalization as an Intervening Variable: Understanding Consumer Behavior in the Era of Algorithmic Personalization - Dini Febriani (JAMI: Jurnal Ahli Muda Indonesia, 2025)
purchasing decisions, with perceived personalization as a mediating variable. This study explores how TikTok users' perception of personalization strengthens the relationship between Live Chat interactions, recommendation algorithms, and purchasing decisions. Methods. This study used a quantitative survey design. The sample consisted of 200 TikTok users in Wonocolo District, Surabaya, who were selected through purposive sampling based on the following criteria: active use of TikTok, interaction with FYP and Live Chat, and making purchases through TikTok Shop. Data were collected using a questionnaire with 20 indicators to measure four latent variables on a 1–5 Likert scale. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Results. The findings show that both the Live Chat feature and the FYP algorithm have a positive influence on perceptions of personalization and purchasing decisions. In addition, perceived personalization proved to be a significant mediator, linking the influence of Live Chat and the FYP algorithm on purchasing decisions. Conclusions This study confirms that perceived personalization is a key psychological mechanism that links user interactions through Live Chat and algorithmic recommendations with purchasing decisions. To increase purchasing decisions on TikTok, an effective personalization strategy integrated with platform features is required.